Uji aktivitas antibakteri ekstrak daun jamblang dari kawasan geotermal: Kadar Hambat Minimum (KHM) dan Kadar Bunuh Minimum (KBM) - Berwi Fazri Pamudi; Munira Munira; Noni Zakiah; Muhammad Nasir (Poltekkes Kemenkes Aceh, 2023)
Background: Jamblang is one of the plants that have the potential to be an antibacterial agent. Jamblang plants can grow in the geothermal area of Ie Seum Aceh Besar. This area has higher soil temperature and pH compared to areas outside of geothermal zones. Environmental conditions influence the chemical composition and pharmacological activities of a plant. Jamblang leaves contain several chemical compounds, including polyphenols, flavonoids, triterpenoids, saponins, and tannins, which function as antibacterials.Objectives: This research aims to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of jamblang leaf extract obtained from the geothermal area of Ie Seum Aceh Besar against Staphylococcus aureus.Methods: The MIC and MBC testing will be conducted using the dilution method with extract concentrations of 1,56%, 3,12%, 6,25%, 12,5%, 25%, 50%, and 100%. The negative control will use distilled water, while the positive control will use amoxicillin. The medium used in this research is Mueller Hinton Agar (MHA).Results: The results indicate that the Minimum Inhibitory Concentration (MIC) of the Jamblang leaf extract grown in the Ie Seum Aceh Besar geothermal area is 50%. In comparison, the Minimum Bactericidal Concentration (MBC) is 100%.Conclusion: The ethanolic extract of jamblang leaves from the geothermal area of Ie Seum Aceh Besar, at a concentration of 50%, inhibited the growth of Staphylococcus aureus. In comparison, at a concentration of 100%, it killed the Staphylococcus aureus.